Impact of outsourcing on company performance study on a local public limited company in Bangladesh - Sarifuzzaman, Md. (BRAC University, 2014)
This dissertation submitted in partial fulfillment of the requirements for the Degree of Masters in Procurement and Supply Management, (IGS), BRAC University